2012
DOI: 10.3945/jn.112.165274
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Treatment Ameliorates Inflammation and Fibrosis in Mice with Nonalcoholic Steatohepatitis3

Abstract: We investigated whether quercetin protects from steatosis and limits the expression of proinflammatory and fibrogenic genes in C57BL/6J mice with nonalcoholic steatohepatitis (NASH) induced by feeding a methionine-choline-deficient (MCD) diet. Quercetin (50 mg/kg) was given by oral route daily. Mice were randomly divided into 4 groups that received for 2 or 4 wk: the control diet plus vehicle, control diet plus quercetin, MCD diet plus vehicle, and MCD diet plus quercetin. At both 2 and 4 wk, feeding the MCD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 57 publications
10
113
0
2
Order By: Relevance
“…These findings were associated with a marked inhibition of HFD-induced TLR-4 expression at transcriptional level and the modulation of TLR-4-NF-B signaling pathway activation by quercetin, and a downregulation of TNF- and IL-6 gene expression, confirming its well-known anti-inflammatory capacity [5,26,59,60]. TNF- and IL-6 play a key role in glucose homeostasis impairment associated with HFD [61], suggesting that proinflammatory cytokines blockage by quercetin contributes to its anti-insulin resistance properties.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 53%
“…These findings were associated with a marked inhibition of HFD-induced TLR-4 expression at transcriptional level and the modulation of TLR-4-NF-B signaling pathway activation by quercetin, and a downregulation of TNF- and IL-6 gene expression, confirming its well-known anti-inflammatory capacity [5,26,59,60]. TNF- and IL-6 play a key role in glucose homeostasis impairment associated with HFD [61], suggesting that proinflammatory cytokines blockage by quercetin contributes to its anti-insulin resistance properties.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 53%
“…TGF-b signals stimulate through transmembrane receptors cytoplasmic Smad proteins, which in turn modulate the transcription of target genes, including those encoding ECM components. 2 In the context of liver fibrosis, Smad3 is pathogenic because mice null for Smad3 are protected against dimethylnitrosamine-induced hepatic fibrosis. 31 Our data demonstrate that the upregulation of TGF-b was associated with increased phosphorylation of Smad3, effects which were partially abrogated by melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…40 We have previously reported that suppression of amphiregulin signals contributes to the protective effects of quercetin in cirrhotic rats with common bile duct ligation, 7 and in mice fed a methionine-choline-deficient diet. 2 It is also known that amphiregulin amplifies the HSC response through increased production of CTGF and TIMP-1. 39 Thus, the inhibition of amphiregulin expression by melatonin in CCl 4 -treated mice supports the suggestion that suppression of the amphiregulin signaling system could be a new target in the prevention of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since the development of fibrosis in liver is progressive and dependent on the activation of hepatic stellate cells, intervals of 24h and 72h are too short to allow observation of significant production of collagen fibers. Other studies with different models of carbon tetrachloride-induced toxic hepatitis 9,18 or a model of methionine-choline deficient diet 19 or studies of arsenite-induced lesions 15 describe attenuation of fibrosis by quercetin. Kawada et al 20 showed that quercetin and other natural phenolics inhibit stellate cell activation by disturbing signal transduction pathways and cell protein expression, thus interrupting the differentiation of stellate cells into myofibroblasts, and the consequent production of collagen type I and II.…”
Section: Effects Of Quercetin On Paracetamol-induced Liver Damagementioning
confidence: 99%